1996
DOI: 10.1149/1.1836971
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Reduction of Lucigenin on Mercury in Aqueous Media

Abstract: A more comprehensive study than those previously reported in the literature was carried out on the electrochemical reduction of 10,10'-dimethyl-9,9'-baicridinium ion (lucigenin) in aqueous solutions. Lucigenin (L') exhibits one, two, or three irreversible voltammetric reduction peaks, depending on its concentration and the scan rate. The first peak is due to the reduction of the first monolayer of molecules adsorbed on the electrode. This process involves two simultaneous one-electron transfers that yield a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…An adsorption layer of viologens on a well-defined electrode surface frequently exhibits a pair of spike voltammetric peaks corresponding to a one-electron redox reaction of the monolayer-level adsorption layer. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] This phenomenon has been understood as being a two-dimensional ͑2D͒ faradaic phase transition. One-electron reduction of viologen to monoradical monocation is accompanied by the formation of the condensed phase.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…An adsorption layer of viologens on a well-defined electrode surface frequently exhibits a pair of spike voltammetric peaks corresponding to a one-electron redox reaction of the monolayer-level adsorption layer. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] This phenomenon has been understood as being a two-dimensional ͑2D͒ faradaic phase transition. One-electron reduction of viologen to monoradical monocation is accompanied by the formation of the condensed phase.…”
mentioning
confidence: 99%
“…One-electron reduction of viologen to monoradical monocation is accompanied by the formation of the condensed phase. [3][4][5][6][7][8][12][13][14][17][18][19] The oxidized dication form of the viologen ͑V 2+ ͒ is usually highly soluble in water, while the one-electron reduced counterpart, monoradical monocation ͑V •+ ͒, is less or sparingly soluble in water. The reduced form tends to form a -stacked dimer.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An adsorption pre‐wave accompanies the first step, while the second one is catalytic, owing to the chemical regeneration of the intermediate reduction product at the electrode surface . A more comprehensive study of the electrochemical reduction of lucigenin in aqueous solutions has been provided later by cyclic voltammetry at a static mercury drop electrode . This study shows that lucigenin exhibits one, two, or three irreversible voltammetric reduction peaks, depending on its concentration and the scan rate (Figure ).…”
Section: Ecl Of Lucigeninmentioning
confidence: 99%
“…Thel ucigenin electrochemicalr eduction reactions in aqueous solutionh ave been evaluatedf or mechanism of ECL by direct current polarography at adropping mercury electrode,b yc yclic voltammetry at an amalga- mated gold electrode and at ahanging mercury drop electrode,a nd by microcoulometry.I t has been found that lucigenin is reduced in two separate one-electron steps. An adsorption pre-wavea ccompanies the first step,w hile the second one is catalytic,o wing to the chemical regeneration of the intermediate reduction product at the electrode surface [17].Amore comprehensive study of the electrochemical reduction of lucigenin in aqueous solutions has been providedl ater by cyclic voltammetry at as tatic mercury drop electrode [18].T his study shows that lucigenin exhibits one,t wo,o rt hree irreversible voltammetric reduction peaks,d ependingo ni ts concentration and the scan rate ( Figure 2). Thef irst peak is attributed to the reduction of the first adsorbed monolayer on the electrode.T his processi nvolvest wo simultaneous one-electron transfers to produce the intermediate radical.…”
Section: Ecl Of Lucigeninmentioning
confidence: 99%